Abu Bakar as-Siddiq The first of the four rightly-guided caliphs - Maulvi Abdul Aziz (Riyadh : Darussalam, 2012)
This book is the first volume in Darussalam's "History of Islam" series, focusing on the life and contributions of Abu Bakr as-Siddiq (R.A), the first of the Four Rightly Guided Caliphs. It aims to provide young readers with authentic and accessible information about Islamic history.
Keywords: Biography, Islam; Islam; Islamic Knowledge